THE EXPERIENCE OF COUNTRIES IN APPLYING NLP METHODS AND TECHNOLOGIES TO THE PROCESSING OF PUBLIC APPEALS - Jurakulov Biloliddin Srojiddinovich (Modern American Journals, 2025)
In recent years, the rapid development of digital technologies and artificial intelligence has led to profound transformations in systems of public administration worldwide. One of the key directions of this transformation is the integration of Natural Language Processing (NLP) methods and technologies into the management of public appeals to state authorities. NLP technologies enable the automated processing, classification, and interpretation of large volumes of textual information, thereby enhancing the efficiency, transparency, and responsiveness of the procedures for handling public appeals.
Keywords: Natural Language Processing (NLP), public appeals to state authorities, digital governance, artificial intelligence, public administration, e-government, automated text analysis, transparency.